Living Waqf Beyond Formal Law: The Mattinja Tradition of Bugis Communities in Jambi’s Plural Legal Landscape - Bahrul Ma'ani; Ardian Kurniawan; Hendri. K; Ilham Abdi Prawira; Rusli Abdul Roni (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study investigates the mattinja practice among the Bugis community in Tangkit, Jambi, as a form of Islamic philanthropy that develops within a context of legal pluralism. While waqf in Islamic law and Indonesian state regulations is typically associated with formal declaration procedures and administrative registration, community-based religious philanthropy often evolves through informal social mechanisms rooted in collective participation and local cultural values. The research analyzes the conceptualization of mattinja in relation to waqf and situates it within the broader frameworks of Islamic philanthropy and living law. Employing a socio-legal approach, the study integrates normative analysis of waqf doctrines with empirical field research in Tangkit, Jambi. Data were collected through field observations and semi-structured interviews with Bugis customary leaders, mosque administrators, religious figures, and community members involved in mattinja practices. The findings indicate that mattinja functions as a collective philanthropic mechanism shaped by Islamic values and Bugis cultural principles such as siri’ na pacce and sipakatau. Although mattinja lacks a formal waqf declaration (sīghah) and state registration, the Bugis community regards it as a long-term religious endowment dedicated to mosque development and communal religious infrastructure. Contributions are commonly interpreted as a form of sadaqah jāriyah, generating ongoing spiritual merit for donors. The article introduces the concept of “living waqf” to describe how waqf-related values operate through socially embedded philanthropic practices outside formal legal institutions within Indonesia’s plural legal landscape